The failed state transition of the ATOLL source GRS 1724–308. Issue 3 (29th March 2018) - Tarana, A; Capitanio, F; Cocchi, M
Abstract: The 2004–2012 X-ray time history of the NS LMXB GRS 1724–308 shows, along with the episodic brightenings associated with the low-high state transitions typical of the ATOLL sources, a peculiar, long lasting (∼300 d) flaring event, observed in 2008. This rare episode, characterized by a high-flux hard state, has never been observed before for GRS 1724–308, and in any case is not common among ATOLL sources. We discuss here different hypotheses on the origin of this peculiar event that displayed the spectral signatures of a failed transition, similar in shape and duration to those rarely observed in black hole binaries. We also suggest the possibility that the atypical flare occurred in coincidence with a new rising phase of the 12-yr superorbital modulation that has been previously reported by other authors. The analysed data also confirm for GRS 1724–308 the already reported orbital period of ∼90 d.